Air pollution in urban environments: implications for citizens´health - Slezakova, Klara (2020)
Currently, 54% of worldwide population lives in urban areas. While growing urbanization causes environmental pollution and energy demand, it has also adverse implications on health, living conditions and lifestyle habits of the respective citizens. To protect human health, numerous organizations have implemented guidelines to limit environmental pollution, or even proposed recommendation on human activity, but how do these translate to the exposure and risks of the respective population? This work aimed to explore how urban development, using time series data from 2015 to 2018, might influence air quality and potential health risks of citizens living in these zones.